IMPROVING HIGH SCHOOL MATHEMATICS TEACHER ABILITY IN MAKING E-MODULE IN PADANG PANJANG CITY - Edwin Musdi (Fakultas MIPA Universitas Negeri Padang, 2019)
Technological development is very possible to use in learning activities for improving the quality of education. Much research has strongly advocated the use and integration of technology in the learning process. One form of utilization of these technologies is the use of E-Modules. E-modules in learning are teaching materials used in assisting learning activities in the form of soft-files that are operated through computers. Interactive e-learning module motivates students to learn more spiritually, actively and independently that can be used by teachers in the learning process. E-Modules allow students to learn not only in the classroom but wherever they are. However, there are many teachers who cannot create or design e-modules. In West Sumatra itself, especially the city of Padang Panjang, e-modules are unknown by teachers. Based on the results of interviews with math subject teachers who are also chairmen of the High School Mathematics MGMP in Padang Panjang City, in general the teachers in the city of Padang Panjang do not know about e-modules and really need training or guidance on e-modules themselves to improve quality their learning in class. Based on this, it was felt necessary to implement an activity program to improve the ability of mathematics teachers in desaining E-Modules in the Padang Panjang city with the partners of Mathematics MGMP. This activity will be facilitated by the IT team who will explain the ins and outs of the E-Module so that technical knowledge about e-modules can be properly controlled by partners. In addition to the IT team this program also involves a team of Mathematics experts who will evaluate the modules designed by teachers during the implementation of the activities so that the quality of modules that can be used by students can be maintained. The mechanism for implementing PKM activities is carried out using action research steps which consist of 4 (four) stages, namely: planning, action, observation and evaluation, and reflection. The implementation of this activity creates e-learning modules that can be designed by subject teachers, especially mathematics.